Association of neopterin as a marker of immune system activation and juvenile rheumatoid arthritis activity - Mones M. Abu Shady; Hanan A. Fathy; Alaa Ali; Eman R. Youness; Gihan A. Fathy (Elsevier, 2015)
OBJECTIVE: To evaluate neopterin plasma concentrations in patients with active juvenile idiopathic arthritis (JIA) and correlate them with disease activity.METHODS: Sixty patients diagnosed as active JIA, as well as another 60 apparently healthy age- and gender-matched children as controls, were recruited from the Pediatrics Allergy and Immunology Clinic, Ain Shams University. Disease activity was assessed by the Juvenile Arthritis Disease Activity Score 27 (JADAS-27). Laboratory investigations were performed for all patients, including determination of hemoglobin concentration (Hgb), erythrocyte sedimentation rate (ESR), and C-reactive protein. Serum concentrations of tumor necrosis factor-alpha (TNF-a), interleukin-6 (IL-6), monocyte chemoattractant protein-1 (MCP-1), and neopterin were measured.RESULTS: Significant differences were found between JIA patients and controls with regard to the mean levels of Hgb, ESR, TNF-a, IL-6, and MCP-1 (p < 0.05). A statistically significant higher mean level serum neopterin concentration (p < 0.05) was found in JIA patients (20.43 ± 8.73 nmol/L) than in controls (6.88 ± 2.87 nmol/L) (p < 0.05). Positive significant correlations were detected between serum neopterin and ESR, TNF-a, IL-6, MCP-1, and JADAS-27 (p < 0.05). No correlation was found between serum neopterin and CRP (p > 0.05). Multiple linear regression analysis showed that JADAS- 27 and ESR were the main variables associated with serum neopterin in JIA patients (p < 0.05).CONCLUSION: The elevation of plasma neopterin concentrations in early JIA patients may indicate stimulation of immune response. Serum neopterin can be used as a sensitive marker for assaying background inflammation and disease activity score in JIA patients.